2019
DOI: 10.1021/acs.orglett.9b02358
|View full text |Cite
|
Sign up to set email alerts
|

C–H Triflation of BINOL Derivatives Using DIH and TfOH

Abstract: C−H trifluoromethanesulfonyloxylation (triflation) of 1,1′-bi-2naphthol (BINOL) derivatives has been established under mild conditions using 1,3-diiodo-5,5-dimethylhydantoin (DIH) and trifluoromethanesulfonic acid (TfOH). Up to eight TfO groups can be introduced in a single operation. The resulting highly oxidized BINOL derivatives can be successfully converted to 8,8′dihydroxy BINOL and bisnaphthoquinone compounds. Mechanistic studies suggested that C−H triflation occurs in the form of an aromatic substitutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…141 Treatment of (S)-BINOL-Me with diiodohydantoin 31 (2 equiv) and TfOH (10 mol %) in CH 2 Cl 2 at 30 °C over 1 h gave the 4,4′,6,6′-tetraiodo product (S)-101 in 74% yield (Scheme 28). 182 This product was characterized by a single crystal X-ray analysis. When an excess amount of TfOH (5 equiv) was used for the reaction, the 8,8′-ditriflated product 102 was isolated in 21% yield with complete racemization.…”
Section: Electrophilic Substitution At 4-positionmentioning
confidence: 99%
See 1 more Smart Citation
“…141 Treatment of (S)-BINOL-Me with diiodohydantoin 31 (2 equiv) and TfOH (10 mol %) in CH 2 Cl 2 at 30 °C over 1 h gave the 4,4′,6,6′-tetraiodo product (S)-101 in 74% yield (Scheme 28). 182 This product was characterized by a single crystal X-ray analysis. When an excess amount of TfOH (5 equiv) was used for the reaction, the 8,8′-ditriflated product 102 was isolated in 21% yield with complete racemization.…”
Section: Electrophilic Substitution At 4-positionmentioning
confidence: 99%
“…The major product was the 6-substituted compound ( S )- 45 . In Scheme , it is shown that when BINOL-Me was treated with excess iodonation agent 31 and TfOH, triflation at the 8,8′-positions can take place to give compounds 102 and 103a – c after the 4,4′,6,6′-positions were substituted . The triflation reaction may be an oxidative nucleophilic substitution by TfO¯ involving a single electron transfer between a hypervalent intermediate like I­(OTf) 3 and the BINOL compound.…”
Section: Electrophilic Substitution At 8-positionmentioning
confidence: 99%
“…In the crystal of 16, 85 additional C-I•••π(arene) interactions outside the search criteria complemented by I⋯O=C halogen bonding interactions lead to a hexagonal array, as described in the original report. 85 In the last structure to be discussed in this section, only one of the four iodide atoms in the tetra-iodide molecule, 17, 86 forms a C-I•••π(arene) interaction, occurring between the two independent molecules comprising the asymmetric unit, Fig. 3(f).…”
Section: Zero-dimensional Aggregates Sustained By a Single C-i•••π(armentioning
confidence: 99%